Studying New Venture Ideas using an Online Funding Platform - Manjiri Kunte; Triyuth Promsiri (Asian Academy of Management Journal, 2019)
Venture ideas in the entrepreneurship process have been studied as a micro-level construct and have been defined in multiple ways in literature. However, previous reviews indicate a lack of studies on the qualities of opportunities or venture ideas and of empirical evidence regarding their effects on entrepreneurial process outcomes. To address this issue, the current study attempts to validate five characteristics of the new venture ideas construct (Davidsson, 2015) towards the outcome variable of the decision to invest or not. The study utilises 80 new venture ideas (projects) from the online funding website. A group of five entrepreneurs rated these ideas independently on novelty, appropriability, diffusability, scalability, and scope, using a 5-point Likert scale ranging from “1 = not at all” to “5 = extremely”. A comparison of the results from regression analysis by the judges and the backers on the funding platform suggested that the characteristic of appropriability was the most important factor in determining the final investment decision. Empirical support for the definition and characteristics of new venture ideas and the validity of appropriability as a significant indicator of the investment decision are the main contributions of this study. The findings of this study will be helpful to both entrepreneurs and investors alike in the future.